Relações filogenéticas e revisão taxonômica das espécies do gênero Copella Myers, 1956 (Characiformes: Lebiasinidae) - Marinho, Manoela Maria Ferreira [UNESP] (2014)
A hypothesis of the phylogenetic relationships of the genus Copella is proposed on the basis of the parsimony analysis of 120 morphological characters found in all the species of the genus recognized as valid in the taxonomic review, and 17 outgroup taxa, most of them members of the family Lebiasinidae. The genus is corroborated as monophyletic based on 38 synapomorphies, of which 13 are exclusive, 19 homoplastic, and six dependent of optimization. Copella arnoldi is the basal taxa, sister of a clade including the remaining species of the genus. The clade represented by Copella nattereri and C. stigmasemion is sister group of the clade (C. eigenmanni (Copella compta and C. vilmae)). Copella is sister of Pyrrhulina, and both are members of the subfamily Pyrrhulininae characterized by having several bony losses and reductions related to the complexity of the sculpturing of their skeleton, especially in Copella and Pyrrhulina, when compared to species of Lebisininae. Based on the results of the phylogenetic analysis and on the observation of the ontogenetic series of several representatives of Lebiasinidae, it is supposed that many morphological traits present in the Pyrrhulininae have evolved through developmental truncation of characters. Based on the analysis of the type material of all nominal species and of a large number of specimens of Copella from several drainages in South America, six out of ten nominal species are recognized as valid: Copella arnoldi, C. compta, C. eigenmanni, C. nattereri, C. stigmasemion, and C. vilmae. Copella arnoldi is considered senior synonym of C. carsevennensis, C. eigenmanni is a senior synonym of C. metae, C. nattereri is a senior synonym of C. callolepis and C. meinkeni, and C. stigmasemion, new combination, is a senior synonym of C. nigrofasciata. The species Copella occur in the rio Amazonas and Orinoco basins, and coastal drainages of Guyana, French Guiana, Surinam, and Venezuela